2016
DOI: 10.1002/ange.201609007
|View full text |Cite
|
Sign up to set email alerts
|

2‐Substituted dATP Derivatives as Building Blocks for Polymerase‐Catalyzed Synthesis of DNA Modified in the Minor Groove

Abstract: 2'-Deoxyadenosine triphosphate (dATP) derivatives bearing diverse substituents (Cl, NH 2 ,CH 3 ,vinyl, ethynyl, and phenyl) at position 2were prepared and tested as substrates for DNApolymerases.The 2-phenyl-dATP was not asubstrate for DNApolymerases,but the dATPs bearing smaller substituents were good substrates in primer-extension experiments,producing DNAsubstituted in the minor groove. The vinyl-modified DNAw as applied in thiol-ene addition and the ethynylmodified DNAwas applied in aCuAACclick reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Streptavidin coated magnetic particles were employed for this task, but significant optimisation was required. Conditions previously reported ( 52 , 70 , 71 ) were not suitable due to the high melting temperature of the TFO-template duplex (∼85°C) and the instability of the streptavidin-biotin interaction above 70°C. ( 70 ) Therefore, conditions that lower the melting temperature of dsDNA, but do not impact the streptavidin-biotin bonds were required.…”
Section: Resultsmentioning
confidence: 99%
“…Streptavidin coated magnetic particles were employed for this task, but significant optimisation was required. Conditions previously reported ( 52 , 70 , 71 ) were not suitable due to the high melting temperature of the TFO-template duplex (∼85°C) and the instability of the streptavidin-biotin interaction above 70°C. ( 70 ) Therefore, conditions that lower the melting temperature of dsDNA, but do not impact the streptavidin-biotin bonds were required.…”
Section: Resultsmentioning
confidence: 99%
“…One key feature (for better or for worse) is also the reversibility of such a bond, cleaved under reducing conditions [ 38 ]. Thiol-ene chemistry was also exemplified by the Hocek group, reaching good coupling yield without the need of UV irradiation [ 39 , 40 ].…”
Section: Chemical Strategies For Post-synthetic Functionalizationmentioning
confidence: 99%
“…However, dNTPs modified with bulky hydrophobic groups such as dibenzylcyclooctyne (DBCO) or large fluorophores such as Cy3 or fluorescein often require a hydrophilic linker such as poly(ethylene glycol) (PEG) to position these groups away from the enzyme's active site. A study of how TdT tolerates modifications at position 2 of dATP found that bulky modifications such as phenyl groups have an inhibitory effect on TdT activity, while smaller modifications such as Cl, NH 2 , CH 3 , vinyl, and ethynyl groups are readily incorporated (Matyašovský, Perlíková, Malnuit, Pohl, & Hocek, 2016). Interestingly, dNTPs with bulky, hydrophobic modifications impart nuclease stability to the modified ssDNA (Gu et al, 2018).…”
Section: Deoxynucleoside Triphosphates (Dntps)mentioning
confidence: 99%